The genetics and biology of the [Het-s] prion of Podospora - Saupe, Sven (Henry Stewart Talks, 2008)
Mammalian prions, Fungal prions, Yeast: [URE3], [PSI+] and [PIN+], Filamentous fungi: [Het-s], Fungal self non-self recognition, Heterokaryon incompatibility, Genetics of [Het-s], Maternal inheritance, Meiotic drive, In vivo and in vitro aggregation of HET-s protein, Role of the Hsp104 chaperone in [Het-s] system, Role of the Hsp104 chaperone in [Het-s] prion propagation, Podospora anserine
Archived at 2021/02/25